The Effect Of Teaching English Vocabulary By Using Animation Video At SMP Swasta Baitul Aziz Bandar Klippa In 2021/2022 Academic Year - Salamuddin Selian, Putri Ayu Lestari, (CV. PUSDIKRA MITRA JAYA, 2021)
This study aims to determine whether there is a significant effect of using animated video media on students' vocabulary skills. This type of research is quantitative research and was conducted using two classes, the experimental class consisted of 28 students and the control class consisted of 30 students. In the data collection technique, the researcher used a pre-test, treatment, and post-test by giving a vocabulary ability test consisting of a pretest of 20 items and a post-test of 25 multiple choice items for each test. The results of this study indicate that there is a significant influence from the use of animated video media. This can be seen from the difference in the average scores of students from the pre-test and post-test in the experimental class which increased from 63 to 90. The average post-test score in the control class was 53 while the post-test score in the experimental class was 90 is higher than the average value of the control class. This means that animated video media can be applied to improve students' vocabulary skills.